2018
DOI: 10.1002/lt.25334
|View full text |Cite
|
Sign up to set email alerts
|

Piggyback or Cava Replacement: Which Implantation Technique Protects Liver Recipients From Acute Kidney Injury and Complications?

Abstract: The cava-preserving piggyback (PB) technique requires only partial cava clamping during the anhepatic phase in liver transplantation (LT) and, therefore, maintains venous return and may hemodynamically stabilize the recipient. Hence, it is an ongoing debate whether PB implantation is more protective from acute kidney injury (AKI) after LT when compared with a classic cava replacement (CR) technique. The aim of this study was to assess the rate of AKI and other complications after LT comparing both transplant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Accumulated experience with different graft/recipient combinations may provide insight into the subtle aspects of each case that will make it more or less challenging. The choice of caval anastomosis technique, surgical efficiency, preparation of the operative field and awareness of the implications of rWIT all undoubtedly impact the implant time [12]. Although the graft selection is done with the best intent of ideal matching, it is not unusual to encounter grafts that are larger than expected, or a hypertrophied right lobe, which makes the caval anastomosis challenging.…”
mentioning
confidence: 99%
“…Accumulated experience with different graft/recipient combinations may provide insight into the subtle aspects of each case that will make it more or less challenging. The choice of caval anastomosis technique, surgical efficiency, preparation of the operative field and awareness of the implications of rWIT all undoubtedly impact the implant time [12]. Although the graft selection is done with the best intent of ideal matching, it is not unusual to encounter grafts that are larger than expected, or a hypertrophied right lobe, which makes the caval anastomosis challenging.…”
mentioning
confidence: 99%
“…The majority of the 18 observational comparative studies 17 , 18 , 19 , 22 , 23 , 31 , 33 , 36 , 40 , 43 , 44 , 48 , 51 , 53 , 54 , 55 , 58 , 59 and two RCTs 5 , 32 demonstrated that the units of PRBCs transfused in the piggyback group was fewer than that of the cava replacement group. No studies demonstrated the units of PRBCs transfused in the cava replacement group was fewer.…”
Section: Resultsmentioning
confidence: 99%
“…This may lead to development of renal injury but this suggestion is still controversial. A retrospective study showed that there was no difference of overall recovery of renal function and survival rates among these LT techniques (24). The team suggested that the amount of transfused red blood cells can be used as a predictor because it correlates to the severity of disease and the complexity of the LT surgery.…”
Section: Discussionmentioning
confidence: 99%